The SFT2D2 gene is associated with the autoimmune pathology of schizophrenia in a Chinese population - Liu, Duilin; Wu, Lin; Wei, Hui; Zhu, Caiyun; Tian, Runhui; Zhu, Wanwan; Xu, Qi (Frontiers in Neurology, 2022)
Background The relative risk of GWAS-confirmed loci strongly associated with schizophrenia may be underestimated due to the decay of linkage disequilibrium between index SNPs and causal variants. This study is aimed to investigate schizophrenia-associated signals detected in the 1q24-25 region in order to identify a causal variant in LD with GWAS index SNPs, and the potential biological functions of the risk gene. Methods Re-genotyping analysis was performed in the 1q24-25 region that harbors three GWAS index SNPs associated with schizophrenia (rs10489202, rs11586522, and rs6670165) in total of 9801 case-control subjects of Chinese Han origin. Circulating autoantibody levels were assessed using an in-house ELISA against a protein derived fragment encoded by SFT2D2 in total of 682 plasma samples. Results A rare variant (rs532193193) in the SFT2D2 locus was identified to be strongly associated with schizophrenia. Compared with control subjects, patients with schizophrenia showed increased anti-SFT2D2 IgG levels. Receiver operating characteristic (ROC) analysis revealed an area under the ROC curve (AUC) of 0.803 with sensitivity of 28.57% against specificity of 95% for the anti-SFT2D2 IgG assay. Discussion Our findings indicate that SFT2D2 is a novel gene for risk of schizophrenia, while endogenous anti-SFT2D2 IgG may underlie the pathophysiology of the immunological aspects of schizophrenia.